The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jssc.201900816
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 14 heterocyclic aromatic amines in meat products using solid‐phase extraction and supercritical fluid chromatography coupled to triple quadrupole mass spectrometry

Abstract: A novel, simple, and sensitive method has been developed for simultaneous determination of 14 heterocyclic aromatic amines in meat product using solid-phase extraction combined with ultrahigh-performance supercritical fluid chromatography coupled to tandem quadrupole mass spectrometry. The analytes could be separated within 7 min and identified using their retention times and mass. The developed method was validated based on the linearity, limits of quantification, precision, and accuracy. The recovery ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…HAAs are created in a heat-dependent reaction between amino acids and sugars, producing pyridine, pyrimidine, or pyrazine, which reacts with creatine (Figure ). More than 25 HAAs are formed in well-cooked red meats. There are multiple chemical subclasses of dietary HAAs, notably aminoimidazoaazarenes (AIA), α-carbolines, and β-carbolines (Table ). AIAs are formed through the heat-catalyzed reaction between amino acids and sugars, producing pyridine or pyrazine, which reacts with creatine.…”
Section: Introductionmentioning
confidence: 99%
“…HAAs are created in a heat-dependent reaction between amino acids and sugars, producing pyridine, pyrimidine, or pyrazine, which reacts with creatine (Figure ). More than 25 HAAs are formed in well-cooked red meats. There are multiple chemical subclasses of dietary HAAs, notably aminoimidazoaazarenes (AIA), α-carbolines, and β-carbolines (Table ). AIAs are formed through the heat-catalyzed reaction between amino acids and sugars, producing pyridine or pyrazine, which reacts with creatine.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1970s, HAAs, a class of mutagenic compounds, were detected in cooked meat ( 12 ). HAAs are a class of nitrogen-containing heterocyclic hazardous substances, and studies have found that more than 25 HAAs are formed in cooked red meat ( 13 , 14 ). In the Maillard reaction system, amino acids, sugars, and creatine are the main components involved in the formation of such culinary toxicants ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 , 15 , 16 ] have been gradually replaced by modern advanced technologies due to their poor sensitivity and selectivity. Chromatographic techniques such as gas chromatography (GC) [ 17 , 18 ], high performance liquid chromatography (HPLC) [ 2 , 19 , 20 ], or capillary electrophoresis (CE) [ 21 ] along with mass spectrometry (MS) are the most commonly used methods. GC-MS is presently popular in quality control laboratories, mainly due to its wide range of applications and relatively inexpensive cost when compared with LC-MS systems.…”
Section: Introductionmentioning
confidence: 99%